Spiritual Citizenship : Transnational Pathways from Black Power to Ifá in Trinidad - Castor, N. Fadeke, 1967- (Book collections on Project MUSE., 2017)
Fadeke Castor explores the roles African religious practice play in the formation of social and political identities play in post-independence Trinidad and Tobago, showing how If#65533;/Orisha practitioners build and perceive a sense of diasporic belonging that leads them to work toward black liberation and a decolonial future.